Metabolic engineering of Mannheimia succiniciproducens for malic acid production using dimethylsulfoxide as an electron acceptor. Issue 1 (29th September 2022) - Lee, Jong An; Ahn, Jung Ho; Kim, Gi Bae; Choi, Sol; Kim, Ji Yeon; Lee, Sang Yup
Abstract: Microbial production of various TCA intermediates and related chemicals through the reductive TCA cycle has been of great interest. However, rumen bacteria that naturally possess strong reductive TCA cycle have been rarely studied to produce these chemicals, except for succinic acid, due to their dependence on fumarate reduction to transport electrons for ATP synthesis. In this study, malic acid (MA), a dicarboxylic acid of industrial importance, was selected as a target chemical for mass production using Mannheimia succiniciproducens, a rumen bacterium possessing a strong reductive branch of the TCA cycle. The metabolic pathway was reconstructed by eliminating fumarase to prevent MA conversion to fumarate. The respiration system of M. succiniciproducens was reconstructed by introducing the Actinobacillus succinogenes dimethylsulfoxide (DMSO) reductase to improve cell growth using DMSO as an electron acceptor. Also, the cell membrane was engineered by employing Pseudomonas aeruginosa cis‐trans isomerase to enhance MA tolerance. High inoculum fed‐batch fermentation of the final engineered strain produced 61 g/L of MA with an overall productivity of 2.27 g/L/h, which is the highest MA productivity reported to date. The systems metabolic engineering strategies reported in this study will be useful for developing anaerobic bioprocesses for the production of various industrially important chemicals. Abstract : Mannheimia succiniciproducens was metabolically engineered to produce malic acid, a four‐carbon dicarboxylic acid of industrial importance. Moreover, reprogramming of the respiration system using dimethylsulfoxide as an electron acceptor and engineering of the cell membrane were performed for enhanced malic acid production. The final engineered strain produced malic acid with the highest productivity reported to date.